Reconstruction of Islamic Epistemology in the Modern Era: A Critical Analysis of the Concept of Islamization of Syed Muhammad Naquib Al-Attas and Its Implications for the Transformation of Islamic Education - Ahmad Khalakul Khairi (Lembaga Bale Literasi, 2025)
This research aims to critically analyze Syed Muhammad Naquib al-Attas's thoughts on the Islamization of science and explore its relevance in the transformation of Islamic education in the modern era. Departing from the dominance of Western epistemology with secular, materialistic, and reductionistic patterns, al-Attas offers the concept of Islamization of science as an effort to reconstruct epistemology based on the principles of monotheism, adab, and spiritual responsibility. This research uses a qualitative approach with a literature study method enriched with philosophical-hermeneutic analysis and critical discourse analysis of al-Attas' main works and relevant contemporary literature. The results of the study show that the concept of Islamization of al-Attas science is not only normative, but has profound epistemological implications in building an integrative knowledge system between revelation and ratio. However, the study also found that the concept faces implementable challenges in the context of modern science based on empiricism. Therefore, this study offers an integrative model of Islamization of knowledge based on the Indonesian educational context that combines the principles of adab with a transformative curriculum approach. The contribution of this research lies in strengthening the theoretical framework of Islamization of science that is more operational and contextual, so that it is relevant for the development of contemporary Islamic education.